2022
DOI: 10.1088/1755-1315/1029/1/012024
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Effects Of Monosodium Glutamate On (NF-κB) Levels In The Male Reproductive System Of Rats

Abstract: Monosodium glutamate (MSG) has been identified as a food additive that Adversely affects MSG use on the reproductive efficiency by several mechanisms, this study was carried out to determine its role in stimulating the immune response in the reproductive system by estimating levels of NF-κB in serum and of its expression in reproductive organs. Thirty sex males rats were used in this study each included 12 male rats. Male rats A and B are receiving 60 and 120 mg/kg for 28 days respectively male rats of the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…Egbuonu et al ( Al-Husseini et al, 2022 ) reported that the ingestion of MSG might adversely alter the functional capacity of the prostate. Another recent study reported the toxic effect of MSG as it caused an elevation in the levels of NFκB in serum, testicular, and epididymis tissue fluid ( Al-Husseini et al, 2022 ).…”
Section: Monosodium Glutamate and The Male Reproductive Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Egbuonu et al ( Al-Husseini et al, 2022 ) reported that the ingestion of MSG might adversely alter the functional capacity of the prostate. Another recent study reported the toxic effect of MSG as it caused an elevation in the levels of NFκB in serum, testicular, and epididymis tissue fluid ( Al-Husseini et al, 2022 ).…”
Section: Monosodium Glutamate and The Male Reproductive Systemmentioning
confidence: 99%
“…Egbuonu et al ( Al-Husseini et al, 2022 ) reported that the ingestion of MSG might adversely alter the functional capacity of the prostate. Another recent study reported the toxic effect of MSG as it caused an elevation in the levels of NFκB in serum, testicular, and epididymis tissue fluid ( Al-Husseini et al, 2022 ). Histological alternation in the reproductive organs was also reported to represent detachment and vacuolation of the seminal epithelium, degeneration of spermatogenesis edema in a lumen in testicular tissues ( Al-Husseini et al, 2022 ).…”
Section: Monosodium Glutamate and The Male Reproductive Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Введення щурам глутамату натрію, який змінює експресію генів центрального осцилятора та активує прозапальні фактори транскрипції, наприклад, NF-κB [31,37], відповідно до наших даних, призводило до значно більшого зниження ШКФ та реабсорбції натрію, ніж це спостерігалося після відтворення ГД на тлі ЛПС-індукованої СЗВ. За даними інших дослідників, за умов природного освітлення щурів лише довготривале споживання глутамату натрію у значно вищій дозі (320 мг/кг маси тіла) виявляє суттєве порушення екскреторної функції нирок, що автори пов'язують з розвитком оксидативного стресу [38].…”
Section: резюме метою цього дослідження було вивчення впливу модулято...unclassified